Lecturers' Perceived Effectiveness of Computer-Assisted Instruction System in Teaching General Studies Courses in Public Tertiary Institutions in Anambra State (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study investigated the effectiveness of Computer-Assisted Instructional Strategies (CAIS) in teaching General Studies (GS) courses in public tertiary institutions in Anambra State, Nigeria. Specifically, it examined lecturers’ perceptions of CAIS in fostering students’ critical thinking, self-confidence, technical proficiency, and learning outcomes, while also exploring challenges and institutional support structures. A mixed-method design was adopted, combining quantitative and qualitative approaches. The quantitative strand employed survey questionnaires administered to male and female GS lecturers, with hypotheses tested using the t-test at 0.05 significance level. The qualitative strand involved semi-structured interviews with lecturers across universities, polytechnics, and colleges of education, thematically analysed to capture experiences and perceptions. Findings revealed that lecturers generally perceived CAIS as effective in enhancing students’ critical thinking, confidence, and digital competence, with mean ratings above the 2.50 benchmark. T-test results showed no significant gender differences in perceptions, suggesting shared experiences across male and female lecturers. Qualitative insights highlighted CAIS as valuable in managing large GS classes, fostering debate and analytical reasoning, and promoting self-confidence, especially through interactive tools, online forums, and multimedia. However, persistent challenges—including epileptic electricity, poor internet connectivity, inadequate ICT facilities, and limited institutional support—significantly constrained CAIS adoption. Lecturers maintained generally positive attitudes toward CAIS but emphasized the need for sustained training, infrastructural development, and supportive policies. The study concludes that CAIS holds strong potential for transforming GS instruction in Nigeria, but institutional investment, equity of access, and capacity-building remain critical for maximising its impact.